Characterization of Rhizosphere Microbial Communities for Disease Incidence and Optimized Concentration of Difenoconazole Fungicide for Controlling of Wheat Dwarf Bunt - Jia, Huanyu; Muhae-Ud-Din, Ghulam; Zhang, Han; Zong, Qianqian; Zhao, Sifeng; Guo, Qingyuan; Chen, Wanquan; Gao, Li (Frontiers in Microbiology, 2022)
Rhizosphere soil microorganisms have great agricultural importance. To explore the relationship of rhizosphere microorganisms with the disease incidence and to optimize difenoconazole fungicide for controlling of wheat dwarf bunt, caused by Tilletia controversa Kühn, the rhizosphere microorganisms were characterized based on sequencing. We found that the disease incidence was correlated with the relative abundance of some microbial communities, such as Acidobacteria, Nocardioides, Roseiflexaceae, Pyrinomonadaceae, Gemmatimonadaceae and Actinobacteria showed significant differences in infected soils compared with control soils and relative abundances of Acidobacteria, Pyrinomonadaceae, Gemmatimonadaceae and Saccharimonadales were distinctly higher in the T. controversa-inoculated group than in the control group. Dehalococcoidia, Nitrosomonadaceae, and Thermomicrobiales were found in only T. controversa-inoculated soil, and these taxa may have potential effects against the pathogen and contribute to disease control of wheat dwarf bunt. Additionally, the soil treated by difenoconazole for T. controversa infected had high relative abundance of Proteobacteria, Actinobacteria, Ascomycota, Basidiomycota, Mortierellomycota and Olpidiomycota based on heatmap analysis and ANOVA. Our findings suggest that the optimized concentration of fungicide (5% recommended difenoconazole) with better control efficiency and constant diversity in the rhizosphere soil.